Antidumping, Retaliation Threats, and Export Prices - Avsar, Veysel (World Bank, Washington, DC, 2013)
Utilizing four-dimensional (firm-product-destination-year) Brazilian firm-level export data, the paper shows that antidumping (AD) duties result in a significant and dramatic increase in the unit values of the products that firms export to duty-imposing countries. Furthermore, it examines the effect of potential (retaliatory) AD duties on the unit price of the firms' shipments. The findings suggest that AD activities in Brazil lead Brazilian exporting firms to increase their unit export prices for the named industries' products to decrease the dumping margin and avoid the threat of retaliation by the target countries.